1994
DOI: 10.1007/bf01541819
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual dysfunction in Indian male patients: Revisited after seven years

Abstract: Short-term (1 year) outcome of 66 male patients with psychosexual dysfunction was studied in the context of patients' sociodemographic and clinical characteristics. A combination of erectile dysfunction and premature ejaculation was the most common diagnosis. Long-term (7 years) outcome of this cohort was evaluated in relation to short-term outcome. Improvement in the short-term indicated favorable long-term outcome. Initial dropout was associated with chronic and continuous sexual dysfunctioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Although some previous studies present similar pattern of data although with variable frequencies,[8910] others have reported PME as a more common disorder. [11] A recent study, from north India, reported DS to be more common sexual disorder (35%), where 32% had DS with ED and 26% had DS with PME.…”
Section: Discussionmentioning
confidence: 52%
“…Although some previous studies present similar pattern of data although with variable frequencies,[8910] others have reported PME as a more common disorder. [11] A recent study, from north India, reported DS to be more common sexual disorder (35%), where 32% had DS with ED and 26% had DS with PME.…”
Section: Discussionmentioning
confidence: 52%
“…Avasthi and his colleagues (1994)[9] conducted an outcome study of 66 male patients with psychosexual dysfunction in the context of socio-demographic and clinical variables. Short term outcome (of one year duration) and long term outcome (of seven years’ duration) of those patients were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…However, scientific research in the area of sexuality in India is scant and, if studied, they have almost exclusively focused on male sexual disorders. (1213) Sexual problems of women have not received adequate attention from the researchers. Worldwide, female sexual dysfunction (FSD) is a highly prevalent problem for 38%-63% of women.…”
Section: Introductionmentioning
confidence: 99%